Relationship Between Teacher-Student Interaction Quality And Learning Interest In Islamic Counseling At Vocational High Schools - Sarwo Edy; Listian Indriyani Achmad; Nenda; Sumarta; Rifqi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The quality of teacher-student interactions in Islamic Guidance and Counseling (BKI) plays an essential role in shaping students' learning interest, particularly in Vocational High Schools (SMK) that emphasize skill-based learning. This study, conducted at SMK Armaniyyah Bekasi, aims to explore the relationship between the quality of teacher-student interactions and students' learning interest in BKI. The main objective is to examine how factors such as communication, emotional support, trust, and empathy from teachers influence students' motivation and engagement in BKI learning. The research employs a quantitative approach with a correlational design, gathering data through questionnaires distributed to students at SMK Armaniyyah Bekasi to assess their perceptions of teacher-student interactions. Additionally, a qualitative approach was implemented through in-depth interviews to provide a more comprehensive understanding of students' experiences. The initial hypothesis suggests that improved teacher-student interactions lead to increased interest in learning BKI. The study's findings are expected to offer valuable insights for educators, helping them enhance their interactions with students and develop learning strategies that cater to both the academic and spiritual needs of vocational school students. Moreover, these results aim to contribute to the development of adaptive curricula and Islamic education practices within vocational education contexts.